2013
DOI: 10.1111/pedi.12100
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c tracking and bio-psychosocial determinants of glycaemic control in children and adolescents with type 1 diabetes: retrospective cohort study and multilevel analysis

Abstract: Early HbA1c predicted future glycaemic control across childhood. Trajectories were further modified by biological factors, exposures to psychosocial adversity, and healthcare use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 40 publications
7
62
1
Order By: Relevance
“…Other studies have also found correlations of glycemic control and household composition, with improved control in those patients whose parents are married and living together vs. single‐parent households . In our study, after regression analysis, there was no significant difference in the rate of single‐parent household between the officer and enlisted groups.…”
Section: Discussionsupporting
confidence: 48%
“…Other studies have also found correlations of glycemic control and household composition, with improved control in those patients whose parents are married and living together vs. single‐parent households . In our study, after regression analysis, there was no significant difference in the rate of single‐parent household between the officer and enlisted groups.…”
Section: Discussionsupporting
confidence: 48%
“…Habituation of the day to day approach to managing chronic disease can make any long-lasting change difficult [34]. Studies involving paediatric and adolescent individuals with type 1 diabetes indicate that age, sex, body mass index, socioeconomic factors, physical activity levels, frequency of glucose monitoring and personality traits can also influence temporal HbA 1c trends [16,[35][36][37]. It may be that a combination of these endogenous and exogenous factors contributes to the phenomenon of tracking and that both need to be addressed for effective long-term glycaemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, previous reports [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] have largely examined individuals with pre-existing type 1 diabetes (i.e. not from the time of diagnosis).…”
Section: Introductionmentioning
confidence: 99%
“…In an early study with youth with T1D, more family stressors (e.g., financial, illness, school, interpersonal) in the previous year were associated with higher A1c [34]. More recent longitudinal studies found that any major life event in the past 3 months (e.g., death/illness in relative, suspension from school, divorce) was associated with accelerated increases in A1c [35, 36]. Among adults with T1D, experiencing more recent stressful life events was associated with worsening glycemic control [37, 38].…”
Section: Dimensions and Types Of Stressmentioning
confidence: 99%